Intra-arterial chemotherapy for locally advanced nasal cavity and sinonasal tract cancers - B. B. Vyzhigina; M. A. Kropotov; B. I. Dolgushin; D. A. Safarov; I. V. Pogrebnyakov; M. T. Isaeva; I. A. Trofimov (Опухоли головы и шеи)
Introduction. Malignant tumors of the nasal cavity and sinonasal tract are rare, less than 3 % of all of the head and neck malignant neoplasm. The leading treatment is combined methods with surgery as a first step. However, operation is limited in a locally advanced process due to requires the use of complex reconstructive techniques and removal of aesthetic and functionally important structures. In this regard, the interest of specialists is understandable in use of organ-preserving techniques with comparable oncological results. Intra-arterial chemotherapy has shown high effectiveness in various localizations of malignant neoplasms, so its use in locally advanced tumors of the nasal cavity and sinonasal tract seems promising.Aim. To evaluate the results of complex treatment of patients with locally advanced cancer of the nasal cavity and sinonasal tract using induction intra-arterial chemotherapy.Materials and methods. The study included 28 from 2017 to 2023 with locally advanced cancer of the nasal cavity and sinonasal tract underwent TPF induction intra-arterial chemotherapy, followed by radiation or chemoradiotherapy. The primary endpoint of the study was survival, secondary – objective response rate, treatment toxicity and the possibility of organ preservation.Results. The median follow-up was 19.1 months. We obtained results for all patients of 1-year overall survival – 85.7 % (T3 – 100 %, T4a – 92.7 %, T4b – 55.6 %), and 1-year progression-free survival – 66.7 % (T3 – 75 %, T4a – 71.4 %, T4b – 50 %), respectively. The response rate after intra-arterial chemotherapy was 85.2 %. Overall survival and progression-free survival did not differ significantly between patients with complete response, partial response, and stable disease. However, in patients with a complete response after chemoradiotherapy, 1-year overall survival was 100 % (p = 0.009) and progression-free survival – 90 % (p <0.001). The main side effect in patients in the study was the development of neutropenia (35.7 %), and occurrence of neurological complications was noted in 10.7 %. Of the 35.7 % of patients with tumor orbital invasion, survival with preserved visual function in the first year of life was 80 %; all patients retained vision; as a result of treatment, not a single patient underwent surgery with exenteration.Conclusion. Induction intra-arterial chemotherapy in treatment of patients with locally advanced cancer of the nasal cavity and sinonasal tract demonstrates high efficiency and a high level of complete responses with a fairly low level of toxicity, and also allows preserve the eye function for the majority of patients.